A high-resolution colorimetric immunoassay for tyramine detection based on enzyme-enabled growth of gold nanostar coupled with smartphone readout. (1st December 2022) - Luo, Lin; Luo, Shuang-Zi; Jia, Bao-Zhu; Zhang, Wen-Feng; Wang, Hong; Wei, Xiao-Qun; Shen, Yu-Dong; Lei, Hong-Tao; Xu, Zhen-Lin; Yang, Jin-Yi
Highlights: Monoclonal antibody specific for tyramine was prepared based on a new hapten design. Alkaline phosphatase enabled the growth of gold nanostars for multicolor generation. A multicolor colorimetric immunoassay for tyramine was developed. Smartphone was used for quantitative detection of tyramine. Abstract: In this work, a specific monoclonal antibody against tyramine was produced based on a new hapten design. Then, we developed a high-resolution multicolor colorimetric immunoassay for tyramine based on this antibody by integrating enzyme-induced multicolor generation with smartphone-assistant signal readout. The multicolor generation is due to the shift of the local surface plasmon resonance band of gold nanostructure controlled by alkaline phosphatase-induced the growth of gold nanostars. Quantitative detection of tyramine was achieved via analyzing the red/blue channel values of assay solution's image taken by a smartphone with the support of a color recognizer application. The limit of detection of this immunoassay for tyramine detection in beef, pork and yoghurt was 19.7 mg/kg or L. The average recoveries were between 83 % and 103 %., and the results were validated by high performance liquid chromatography to be reliable. Overall, this developed immunoassay provides a promising platform for on-site detection of tyramine.